Supporting reading instruction through the use of assistive technological devices for students with learning disabilities (2018)
Many students are being identifìed with learning disabilities as a result of unexpected underachievement that cannot be explained by sensory impairments, cognitive or intelectual disabilities. This condition has put teachers under pressure because they are saddled with the responsibility of providing quality education to all learners in their classrooms, including those with learning disabilities. In view of this, it is believed that the achievement of students with learning disabilities can only be maintained and/or improved by providing moderate to high levels of effort and support. A typical example of instructional support that the school can provide to students with learning disabilities is the use of assistive technological devices for reading instruction. This paper therefore, examined the different kinds of assistive technological devices that teachers of students with learning disabilities can adopt for effective teaching of reading to students. The study is anchored on the SAMR (Substitution, Augmentation, Modification, Redefinition) model of classifying the use of technology in education. It also analysed typical technology-based interventions effective for supporting reading and reading instruction of students with learning disabilities. It is recommended that to use assistive technological devices effectively for reading instruction, teachers of students with learning disabilities should understand learners’ differences, identify student specific barriers that occur during reading instruction and assessment that can be remedied through technology and adopt appropriate assistive technological tools to remove barriers in reading. Students with learning disabilities should be given proper orientation towards the use of assistive technological devices for reading to enable them adopt the devices and advocate for the use of specific technologies.